Femicide Framing and Ethics Violation on Indonesian Instagram News Contents - Wahyujati, Bertha Bintari; Herawati, Fransisca Anita (Jurnal ILMU KOMUNIKASI, 2025)
Femicide cases in Indonesian newspapers are reported as ordinary criminal news. The study applied content analysis to Instagram news captions, examining indicators of violations of the Journalistic Code of Ethics and framing using Entman’s theory. Instagram captions serve as previews, directing users to full news links. Findings show that several accounts violated ethical standards by exposing victims and suspects, engaging in victim-blaming, and prioritizing virality. Femicide cases, framed as ordinary crimes, tend to blame victims within a patriarchal system.